Knowledge, Attitude and Use of Cooking Oil on Traders Around Esa Unggul University - Fenny Anngraeny Nasution; Laras Sitoayu; Putri Ronitawati (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
Use cooking oil for everyday cooking very often used it makes the majority of community especially the food trade is highly dependent on cooking oil. Cooking oil serves as a conductor of heat, savory flavor enchancer, and adding value calorie fried foods. This study aimed to determine the relationships of knowledge, attitude, and use of cooking oil at taders around University Esa Unggul. This research is an analytical survey with cross sectional Study design. The data were obtained using questionnaire. Data processing using Chi Square Test with a confidence level of 95% and α = 0,05. This study conducted in Desember 2016 till Febuary 2017. This study population all traders in Universitasy Esa Unggul with sample 45 peoples. There is a relationship between knowledge an use of cooking oil p value 0.011 (p0.05) and there is a relationship attitude and use of cooking oil p value 0.024 (p0.05). Keywords: attitude, cooking oil, knowledge, trader